2011
DOI: 10.1371/journal.pone.0025631
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Survival Time Prediction for Patients with Glioma Is Improved by Measuring Mitotic Spindle Checkpoint Gene Expression

Abstract: Identification of gene expression changes that improve prediction of survival time across all glioma grades would be clinically useful. Four Affymetrix GeneChip datasets from the literature, containing data from 771 glioma samples representing all WHO grades and eight normal brain samples, were used in an ANOVA model to screen for transcript changes that correlated with grade. Observations were confirmed and extended using qPCR assays on RNA derived from 38 additional glioma samples and eight normal samples fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 69 publications
5
49
0
Order By: Relevance
“…Consistent with prior reports, we found CDC20 mRNA is significantly elevated in glioblastomas compared to normal brain (Figure 5A) (Bie et al, 2011; Marucci et al, 2008). We then assessed CDC20 expression in the four TCGA-based molecular subtypes—Proneural, Mesenchymal, Classical, and Neural—and found the Proneural subtype demonstrated significantly higher CDC20 expression compared to the other subtypes (Figure 5B) (Verhaak et al, 2010).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with prior reports, we found CDC20 mRNA is significantly elevated in glioblastomas compared to normal brain (Figure 5A) (Bie et al, 2011; Marucci et al, 2008). We then assessed CDC20 expression in the four TCGA-based molecular subtypes—Proneural, Mesenchymal, Classical, and Neural—and found the Proneural subtype demonstrated significantly higher CDC20 expression compared to the other subtypes (Figure 5B) (Verhaak et al, 2010).…”
Section: Resultssupporting
confidence: 93%
“…CDC20-APC has been viewed as a potential strategic target in several human cancers (Wang et al, 2015). CDC20 mRNA is elevated in glioblastoma compared to low-grade gliomas, and CDC20 immunoreactivity in gliomas correlates with pathological grade, but little is known about the biological roles of CDC20-APC in glioblastoma (Bie et al, 2011; Marucci et al, 2008). Recent studies have revealed unexpected non-mitotic roles for CDC20-APC in the developing mammalian brain, indicating CDC20-APC executes functions beyond the cell cycle (Kim et al, 2009; Puram et al, 2011; Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-cycle regulator CDC20 that is often upregulated in several malignancies (30) and indirectly regulated by p53, is downregulated under AEBP1 downregulated condition, whereas p53 itself is upregulated. Interestingly CDC20 has also been associated with prognostic behavior of glioma patients (37). Again CDK6, an established marker associated with GBM (38,39), is also affected by AEBP1 downregulation.…”
Section: U87mg U138mgmentioning
confidence: 98%
“…Loss of SAC function is a common explanation proffered for increased chromosome instability and aneuploidy in cancers (25-27). This notion that loss of SAC activity promotes tumorigenesis has found support in studies of certain cancers (25,26) and model systems (e.g., mouse knockouts of certain SAC genes) (23, 28). However, loss of function mutations in SAC genes are rare in cancers (27), and many late-stage cancers exhibit high SAC gene expression (29, 30), suggesting hyperactivity (30,31).…”
Section: Introductionmentioning
confidence: 80%